PROFIL LITERASI LINGKUNGAN SISWA DALAM MENDUKUNG SDGS DI SEKOLAH DASAR - Yuliasih, Danik Fida; Suryanti; Ganes Gunansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe elementary school students' environmental literacy level in supporting the achievement of Sustainable Development Goals (SDGs). The subjects of the study included students of SDN Rejeni, SDN Sedati Gede II, and SDN Kedungpandan I. The instrument used was an environmental literacy questionnaire covering four domains: ecological knowledge, attitudes towards the environment, cognitive skills, and pro-environmental behavior. The results showed that aspects of students' knowledge and attitudes were in the high category, while cognitive skills and pro-environmental behavior were still classified as moderate. To overcome these weaknesses, learning media are needed that not only convey information but also train critical thinking and encourage real action. LKPD based on Project-Based Learning (PjBL) is considered appropriate because it can integrate aspects of knowledge, attitudes, skills, and behaviour thematically and contextually. Through the implementation of LKPD based on PjBLl, students are expected to be more active, reflective, and care about the environment sustainably.